COMPUTER SECURITY - Glīzds, Lauris; Teilāns, Artis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The paper contains information about hacking types and systems which they are suffered the most cyber attack. The main goal is to introduce people how to protect your systems from several cyber attacks following by special guidelines.